AN ALTERNATIVE METHOD OF CALCULATION OF ELECTROMAGNETIC WAVE RADIATION FIELD IN THE MOBILE COMMUNICATION SYSTEM - M. Melibayev (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: In the Mobile connection system radiation field calculation methods are considered.